Journal of Politeness Research : Language, Behaviour, Culture (De Gruyter Mouton, 2005)
The Journal of Politeness Research broadens and sharpens the understanding of the nature of politeness by providing a much-needed forum for synergies to develop between researchers approaching politeness from different disciplinary angles. The journal also strengthens and widens the existing cross-cultural and intercultural body of politeness research by encouraging new contributions from lesser-studied cultures and languages.